Pleasantness shapes congruency effects in odor-induced taste enhancement - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Spatiotemporal heterogeneity and teleconnection drivers of abrupt dry–wet transitions across the Tibetan Plateau - Qiman Gong; Xingjiao Zhang; Shiqi Ao; Yuanwei Wang; Lei Wang; Xiaoyu Guo; Ting Li; Zhaoyan Xie; Sichen Lin; Lin Zhao (Atmospheric Research, 2026)

Chronic paternal exposure to low-dose OBS reprograms progeny's intestinal cholesterol metabolism and increases IBD susceptibility - Wang Yang; Yongsheng Teng; Zeyu Yang; Xiaomei Song; Le He; Yan Liu; Wei Tan; Huihui An; Ping Shi; Chaoqun Hu; Lin Ao; Hong Guo (Environmental Pollution, 2026)

A cascade reaction pathway enabled by sub-micron bismuth-decorated cathode for aqueous Zn-I2 batteries - Zhuoran Ao; Huixin Ren; Yuxi Guo; Lijing Yan; Zhan Lin (Chemical Engineering Journal, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Establishing robust chronologies in mangrove sediments in Southeast China with synergistic application of 210Pb and dual 137Cs markers - Shengbin Ye; Qiangqiang Zhong; Conghe Zhang; Shanshan Song; Xin'ao Guo; Neil Saintilan; Guanghui Lin (Quaternary International, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

Sustained decrease in snowfall over the Tibetan Plateau under a changing climate - Sichen Lin; Zhaoyan Xie; Yuanwei Wang; Lingxiao Wang; Lei Wang; Xiaoyu Guo; Chenhao Chai; Ting Li; Shiqi Ao; Xingjiao Zhang; Lin Zhao (Global and Planetary Change, 2026)

Digitalization of wheat mold odor based on controlled volatile release: A large-scale study - Xiaogang Liang; Qiaofen Chen; Qinqin Li; Jinyin Zhang; Yun Yang; Geni Hou; Haiwen Peng; Wei Ao; Lin Lin; Jianmin Wu (Food Chemistry, 2026)

The evolution of immobilized enzyme technology: from “single method” to “composite strategy fusion”: A review - Qi Ao; Fan Wu; Lin Jiang (Chemical Engineering Journal, 2026)

In situ iron isotopic analysis of mantle silicate minerals by fs-LA–MC–ICP–MS - Xinting Lü; Detao He; Yongsheng Liu; Huajiang Liang; Chunfei Chen; Kexin Deng; Xi Zhu; Ming Li; Yansheng Lai; Ao Yang; Jie Lin; Zhaochu Hu (Chemical Geology, 2026)

Effect of size-dependent mixed-wettability on pore-scale immiscible displacement dynamics: A numerical study - Yusong Xu; Bo Shui; Zidi Lin; Li’ao Su; Zhaolin Gu; Junwei Su (Advances in Water Resources, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

A novel parameter identification method for disc-shaped AUVs using mixed-excitation CFD - Zhipeng Lin; Yuehua Chen; Gang Zhang; Xian'ao Jia; Jiwei Wang (Ocean Engineering, 2026)

Targeting Peroxiredoxin 6: Tannic Acid Inhibits Singapore Grouper Iridovirus Infection via PRDX6‐Dependent Pathway and Antioxidant Response - Xiangmou Qin; Chen‐Ao Li; Lin Huang; Qing Yu; Mingming Zhao; Yanxia Gao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; Junxiang Lai; Ermeng Yu; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a major viral pathogen threatening grouper aquaculture. The lack of specific antiviral drugs underscores the urgent need to develop safe and effective control strategies. This study demonstrates that tannic acid (TA) exhibits significant anti‐SGIV activity in vitro. In grouper spleen (GS) cells, TA inhibited SGIV replication in a concentration‐dependent manner. Time‐of‐addition assays confirmed its antiviral efficacy when applied either before or after SGIV infection. Mechanistically, TA directly interfered with SGIV particle infectivity, viral adsorption, entry and intracellular replication. Network pharmacology analysis suggested TA's targets are associated with host cellular antioxidant pathways, among which Peroxiredoxin 6 (PRDX6) was identified as a potential target of TA. Further experiments confirmed that TA upregulated the Nrf2 antioxidant pathway and suppressed the expression of pro‐inflammatory cytokines (IL‐1β, IL‐8). Notably, TA enhanced the expression of PRDX6, and overexpression of PRDX6 significantly inhibited SGIV replication, indicating that PRDX6 contributes to the antiviral effect of TA. In vivo, TA treatment not only restored PRDX6 expression in infected groupers but also significantly reduced viral load in liver and spleen following SGIV infection. These findings demonstrate that TA inhibits SGIV through direct viral interference and PRDX6‐mediated antioxidant modulation, highlighting its potential as a natural therapeutic agent against SGIV.

Temporal scale dictates the dominant driver of lake dynamics on the Tibetan Plateau - Ting Li; Yuanwei Wang; Lingxiao Wang; Lei Wang; Jing Zhou; Xiaoyu Guo; Jie Xu; Chenhao Chai; Zhaoyan Xie; Sichen Lin; Shiqi Ao; Xingjiao Zhang; et al. (Journal of Hydrology, 2026)

Ferritin Associates with Interspecific Variation in Iron Accumulation among Five Economically Important Bivalves: Sequence, Expression, and Functional Analyses - Jiachen Li; Ao Li; Zizheng Wei; Zhihua Lin; Liyuan Lv; Hanhan Yao; Yinghui Dong (Biological Trace Element Research, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Expanded coverage of N-acyl amino acids using one-pot micro synthesis-chemical derivatization-LC-MS strategy: A key to bioactive compounds analysis in fermented soybean - Jie Han; Yujie Li; Lanjia Ao; Li Zhang; Tingting Zhou; Na Li; Jian-Lin Wu (Food Chemistry, 2026)

Self-assembling gardenia pectin gel for cholestatic liver injury: Dual mechanisms of hepatoprotection via PPARα activation and gut microbial modulation - Lanjia Ao; Yujie Li; Lingling Zheng; Xiaolin Chen; Haoyuan Zeng; Wen Miao; Shuxian Yang; Tingting Zhou; Na Li; Jian-Lin Wu (Carbohydrate Polymers, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Sustained Intra-Articular Delivery of Triple Therapeutics Using a Phase-Transition Phospholipid-Based Gel for Effective Treatment of Gouty Arthritis - Sirui Ma; Jing Yang; Ao Li; Qing Lin; Tao Gong (Pharmaceutical Research, 2026)

Epigallocatechin Gallate (EGCG) Inhibits Singapore Grouper Iridovirus (SGIV) Infection by Interfering With Viral Life Cycle and Modulating Host Cell Cycle G2/M Checkpoint - Tianhong Zhao; Jinkun Xie; Chen‐Ao Li; Mingzhu Liu; Qing Yu; Lin Huang; Yanxia Gao; Mingming Zhao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a highly pathogenic virus that causes substantial economic losses in marine grouper aquaculture, and effective antiviral agents are currently lacking. In this study, the anti‐SGIV activity of epigallocatechin gallate (EGCG), a natural compound from green tea, was evaluated and its underlying mechanisms were investigated. Cytotoxicity assays showed that EGCG at concentrations up to 12.5 μg/mL was safe for grouper spleen (GS) cells. EGCG treatment reduced viral MCP and VP19 mRNA expression in a dose‐dependent manner, indicating its anti‐SGIV activity. Mechanistic studies revealed that EGCG directly impaired SGIV particle infectivity and interfered with viral adsorption, entry, and intracellular replication. Network pharmacology analysis identified overlapping genes between EGCG targets and SGIV‐induced differentially expressed genes, with enrichment pathways related to cell cycle regulation, particularly the G2/M checkpoint. Further studies showed that SGIV infection upregulated the G2/M checkpoint regulators WEE1 and CHEK2, and EGCG treatment reversed these dysregulations, suggesting that EGCG alleviates SGIV‐induced G2/M arrest. In vivo, EGCG treatment significantly reduced viral load in infected groupers and improved survival rate. Collectively, these findings demonstrate that EGCG exerts potent anti‐SGIV activity both in vitro and in vivo by directly targeting multiple steps of the viral life cycle and modulating host cell cycle G2/M checkpoint pathways, highlighting its potential as a natural therapeutic agent against SGIV infection.

Two-step single B cell technology for high-affinity rabbit monoclonal antibodies: development of a highly sensitive immunoassay for monensin in raw milk - Jingjie Huang; Ao Lin; XinXin Ma; Yanzhe Qing; Yani Gu; Xiaole Pan; Jiancheng Li (Food Chemistry, 2026)

CaIRF1 promotes antibacterial immune defense and acts as a vaccine adjuvant in Chromileptes altivelis - Guotao Wang; Ying Wu; Jue Lin; Chen Zhang; Zhenjie Cao; Jingqun Ao; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2026)

InceptionFormer: A deep learning framework for UAV LiDAR point cloud completion to improve tree parameters estimation in dense forests - Binhan Luo; Jian Yang; Shuo Shi; Ruilin Gan; Zhongliang Wu; Sihao Wang; Ao Wang; Lin Du; Wei Gong (Remote Sensing of Environment, 2026)

Nanoimprinted topological laser in the visible - Qiang Zhang; Rui Duan; Yutian Ao; Lin Wang; Xuehong Zhou; Xuyong Yang; Qing Zhang; Xiao-Cong Yuan; Baile Zhang; Handong Sun (Science Bulletin, 2026)

Co-occurrence and regulation of nanoplastics and typical flame retardant in anammox process: Potential risk and molecular mechanism - Jing-Ao Jin; Na-Na Han; Wei-Lin Guo; Qiu-You Xu; Jiao-Jiao Wang; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Selective separation of bismuth from high-acid copper electrolytes: design of highly stable antimony-based adsorbent and investigation of strong adsorption mechanisms - Ao Gong; Yingdan Lin; Zixuan Zhang; Guangping An; Zheqiu Zhang; Zanhui Fu; Bin Zeng; Kuifang Zhang; Zhifeng Xu (Journal of Cleaner Production, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Surface piezotronics in centrosymmetric silicon for ultra-sensitive strain sensing and mechanoelectronic transduction - Mingqiang Zhong; Shaopeng Wang; Tianli Meng; Ao Li; Jiale Lv; Ehud Gazit; Zhong Lin Wang; Rusen Yang (Chemical Engineering Journal, 2026)

Design and synthesis of novel fucosylated chondroitin sulfate derivatives as intrinsic FXase inhibitors and evaluation of their antithrombotic activities - Dongliang Xu; Xi Gong; Lisha Lin; Hang Dong; Yijian Wen; Yingnian Li; Gang Fu; Yuanhang Ma; Weicheng Xiong; Tianyu Guan; Ao Sun; Xiangbao Meng; et al. (Carbohydrate Polymers, 2026)

Y/Ho ratios in marine sediments unveil Neoproterozoic ocean acidification - Yong-Sheng Liu; Wen-Shuai Li; Jun-Bo Zhang; Jie Lin; Ao Yang; Lian Zhou; Dai-Du Fan; Xi Zhu; Ying-Hua Zhang (Science Bulletin, 2026)

Construct dichlorine monoxide equilibrium at high chloride concentrations to reveal its overlooked reactivity and unique site-selectivity in degrading micropollutants - Chuanjing Lin; Binghua Jing; Yixiao Duan; Zexuan Ma; Lulu Li; Zhimin Ao; Chii Shang; Li Ling (Journal of Hazardous Materials, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Temporal demographic compensation stabilizes pioneer conifer (Pinus massoniana) populations during ecological restoration - Yongwei Luo; Ao Liu; Bingqi Hu; Jinlian Liu; Qifeng Gong; Yan Lin; Jianqiang Rao; Shouzhong Li (Forest Ecology and Management, 2026)

Enhancing taste without salt or sugar: Cross-modal flavor modulation via olfactory cues - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Polycyclic aromatic hydrocarbons-induced suppression of the PPARα/ACAA1 axis drives hepatic steatosis: Integrating epidemiology, network toxicology, and experimental validation - Haonan Cui; Peng Zou; Wang Yang; Shijun He; Jinyuan Shi; Ting Sun; Mengge Wang; Zhiyong Song; Hanni Guan; Tong Wang; Lei Sun; Qing Chen; et al. (Chemico-Biological Interactions, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

From hydrogeochemical genesis to public health risk: Unveiling the links between geogenic arsenic, fluoride, and iodine in groundwater - Furong Yu; Ao Li; Rui Li; Lin Wu; Deng Pan (Journal of Hazardous Materials, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

Integrative metabolomics-assisted comprehensive components analysis of complex system (CCACS) revealed functional potential: Valorization of gourd fruit (Trichosanthes kirilowii maxim.) - Wen Miao; Na Li; Lanjia Ao; Yujie Li; Ying Liu; Yiran Zhao; Xiaolin Chen; Yuyao Wu; Jian-Lin Wu (Food Research International, 2026)

Mussel-inspired bioadhesive via enzymatic adhesive peptide synthesis and liquid-liquid phase separation for robust adhesion in harsh environments - Siqiang Wang; Kai Li; Zitang Xu; Hao Wang; Qiyang Wang; Ao Lin; Pengbo Wang; Xiaoman Xie; Li Xu; Yunjun Yan (Chemical Engineering Journal, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Hop bitter acids from the pistillate flower of Humulus lupulus L. and their anti-inflammatory and anti-dengue virus activities - Biao Sun; Yun-Lin Ao; Xia Cao; Jia-Bing Zhang; Xia Zhang; Dong-Hao Lu; Man Lin; Jun-Shan Liu; Xiao-Qi Zhang (Phytochemistry, 2026)

Predictive modeling of high-speed ice-structure interaction using PD-AE-LSTM - Ming He; Mengshan Xie; Yu Ao; Xinran Li; En-Fan Lin (Ocean Engineering, 2026)

Pathogen-driven modulation of eight STATs in Cromileptes altivelis: Comparative analysis from homeostasis to immune activation - Panpan Zhang; Shuyi Lin; Zixin Xie; Guisen Chen; Zhenjie Cao; Chen Zhang; Jingqun Ao; Yongcan Zhou; Ying Wu; Yun Sun (Fish & Shellfish Immunology, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Mechanistic insights into electric field-assisted nanofiltration for efficient lithium-magnesium separation - Ao Wang; Dimitrios Toroz; Xiaofu Guo; Jie Liu; Shangming He; Liting Fei; Yingying Zhao; Shizhao Wang; Junsheng Yuan; Devis Di Tommaso; He Lin; Fei Li; et al. (Water Research, 2025)

Evaluation of reclaimed treated wastewater on soil quality, microbial community and function in urban greening irrigation - You Zhou; Lin Chang; Hui Sun; Wei Li; Tianqi Ao; Jin Lin (Journal of Environmental Management, 2025)

A computationally driven screening-construction-mechanism strategy of magnetic molecularly imprinted polymers for aliphatic aldehydes detection - Yongqing Zhang; Xiaolong Shang; Jiaqi Guo; Ling Ao; Caihong Shen; Miao Liu; Feng Lin; Wenxian Li; Liqiang Zhang; Baoguo Sun; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

A versatile hydrogel for sensing-energy storage integrated wearable electronics - Kunlong Huang; Junyi Zhou; Ao Xiao; Bin Lin; Zhiyun Huang; Tianmin Wu (Chemical Engineering Journal, 2025)

Ultra-durable and long-cycle fire alarm system for intelligent fire protection - Xing Zheng; Hongjie Lin; Mingyu Liu; Ao Cai; Wenhua Chen; Pengju Liu; Hao Huang; Yuan Liu (Chemical Engineering Journal, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Preparation of porous thermoresponsive coating (PU@AC-Al) and its synergistic mechanism of early fire warning and flame retardancy - Ting Wang; Wei Lu; Jinliang Li; Jinhu Li; Ao Gao; Jianjun Lin (Process Safety and Environmental Protection, 2025)

Paleo-Asian Ocean subduction-related multiple mantle metasomatism: Constraints from in-situ Sr Mg isotopes of mantle xenoliths in the Xing-Meng orogenic belt - Xudao Liu; Kaizhang Yu; Yongsheng Liu; Zhicheng Liu; Chunfei Chen; Jie Lin; Ao Yang; Xi Zhu; Zhaochu Hu (Lithos, 2025)

Understanding the pollutant molecular fate in a two-stage biological-coagulation-membrane distillation hybrid process for treating hypersaline organic wastewater - Ao Wang; Hang Xu; Chen Yao; Tianlong Hu; Jingjun Wang; Tao Lin; Hui Tao; Mingmei Ding (Desalination, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Site-selective hydroxyl functionalization: A dual-functional strategy for fabricating porous cellulose molecularly imprinted fiber for in vivo piperacillin sodium analysis - Deng Li; Min Wang; Zhou Li; Jia Zeng; Yingxi Zhu; Jiahao Lin; Zuojin Ao; Famin Ke; Kailian Zhang; Die Gao; Dandan Wang (Analytica Chimica Acta, 2025)

Early Pleistocene integration of the Yellow River III: Paleontological and paleohydrological evidence from the Fenwei Basin - Guoqiao Xiao; Xinru Lin; Tianran Chen; Qing Pan; Hong Ao; Yange Wang; Meiyan Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

A precisely regulated Streptomyces expression system pTZYp facilitated by the strong promoter stnY and cmt operon - Kai Zhang; Ao-yu Wang; Qiang Zhou; Yi-feng Chen; Shuang-jun Lin; Gong-li Tang (Biotechnology Letters, 2025)

Advanced fluidized bed-ultrafiltration-reverse osmosis process for near-complete fluorine recovery from photovoltaic fluoride-laden wastewater: system parameters and mechanisms - Ao Wang; Hangang Xie; Hang Xu; Wenwen Huang; Jun Ma; Tianlong Hu; Jingjun Wang; Tao Lin; Mingmei Ding (Water Research, 2025)

Occurrence, removal and ecological risk assessment of antibiotics in rural domestic wastewater treatment systems in the Beijing-Tianjin-Hebei region - Hongliang Wang; Sai Zhang; Ziyu Lin; Feifei Xiao; Bao Xiang; Ao Li (Journal of Hazardous Materials, 2025)

Efficient recovery of spent catalysts in PAO production via annular drainage hydrocyclone: a sustainable approach for fluorinated waste reduction - Wei Zhao; Jian-ping Li; Tong Zhang; Shu Zhu; Ao-song Wei; Dan-hui Yang; Xue-jing Yang; Hua-lin Wang (Journal of Cleaner Production, 2025)

Linkage site regulation on photocatalytic hydrogen evolution performance of naphthalene-based conjugated polymers - Xufeng Ji; Nan Chen; Jinlian Yuan; Ao Sun; Lin Zhou; Xing Ding; Yi Yang; Bo Chai; Deng Ding; Xiaohu Zhang; Ke Dai; Hao Chen (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Structural optimization and mechanical property analysis of butterfly valves based on Kriging surrogate model - Lei Shi; Tao Yang; JiangYan Ma; Lin Huang; Ao Tian; Yang Xuan; Yan Tian; Ran Gao (Building and Environment, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Antibacterial and antioxidant activities of β-glucans derived from Aureobasidium pullulans - Junqiu Ao; Yuqing Liu; Yanyu Wei; Dahui Wang; Chonglong Wang; Lin Wei; Gongyuan Wei (Food Bioscience, 2025)

Automating refined on-site construction carbon emissions calculation for prefabricated buildings based on BIM: Model development and validation - Zujian Huang; Yang Zhao; Hao Zhou; Hao Tang; Ao Luo; Peijun Lu; Yicheng Wang; Borong Lin (Environmental Impact Assessment Review, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Regulation of electrode surface microenvironment by porous ion transport layer for High-Efficiency CO2 electrochemical reduction to ethylene - Hao-Yan Shi; Yan-Xin Chen; Yi-Hu Pu; Hai-Long Wang; Yi-Zhan Xie; Xin-Zhi Tian; Yang Yang; Ao-Sheng She; Wen Chen; Wei-Hua Yang; Xiu-Mei Lin; Can-Zhong Lu (Chemical Engineering Journal, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

A deep learning model based on data decomposition and modern convolution for predicting influent characteristics of wastewater treatment plant - Lin Gan; Ao Li; Ji Li; Zhizhang Shen (Journal of Water Process Engineering, 2025)

Membrane fouling alleviation by thermal activation of hydrogen peroxide-membrane distillation hybrid system: Insights into interfacial phenomena and NOM-ion interactions - Ao Wang; Hang Xu; Chen Yao; Jun Ma; Jingjun Wang; Tianlong Hu; Dingwen Zong; Tao Lin; Mingmei Ding (Desalination, 2025)

Urea-crosslinked 3D graphene oxide/MXene-SO3/cyclodextrin films for efficient and sustainable biodiesel production - Qi Ao; Lin Jiang; Jun Tang (Carbohydrate Polymers, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Low-level exposure to environmental lithium element affects male reproductive outcomes: Results from the MARHCS cohort study in Chongqing, China and in vivo animal experiments - Lihong Wang; Guanghui Zhang; Xi Ling; Mei Wan; Qing Chen; Lei Sun; Huan Yang; Tong Wang; Jinyi Liu; Jia Cao; Lin Ao; Peng Zou (Reproductive Toxicology, 2025)

Oxidation extraction of copper from chalcopyrite powered by ultrasound enhanced free radical mechanism - Zhuoyu Yin; Dekun Zhang; Lun-Ao Ouyang; Likang Fu; Yonggang Zuo; Shixing Wang; Gengwei Zhang; Guo Lin; Hongying Xia; Libo Zhang (Process Safety and Environmental Protection, 2025)

Construction of a highly sensitive recoverable lipase@sodium alginate/cyclodextrin/graphene oxide film for triglyceride detection in dairy products - Qi Ao; Ziran Chen; Lin Jiang; Weiwei Jin (Chemical Engineering Journal, 2025)

UCHL1-Mediated Spastin Degradation Regulates Microtubule Severing and Hippocampal Neurite Outgrowth - Ao Ma; Zhi Liang; Hongde Zhang; Zhichao Meng; Jiehao Zhu; Shu Chen; Qisheng Lin; Tao Jiang; Minghui Tan (Journal of Molecular Neuroscience, 2025)

WTAP-mediated m6A modification of Hmgb2 contributes to spermatogenic damage induced by PM2.5 exposure - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Chaofeng Shi; Tong Wang; Lei Sun; Lin Ao; Fei Han; Qing Chen; Jia Cao; Jinyi Liu (Environmental Pollution, 2025)

Enhancing rejection of short-chain per- and polyfluoroalkyl substances by tailoring the surface charge of nanofiltration membranes - Yue Zhi; Xiaoqing Zhao; Ao Shuai; Yonghui Jia; Xinyi Cheng; Shihong Lin; Feng Xiao; Le Han; Hongxiang Chai; Qiang He; Caihong Liu (Water Research, 2025)

BarH1 regulates the expression of conserved odorant-binding protein 22 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Ao Liu; Yi Wei; Rui-Lin Zhang; Hazem Abdelnabby; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2025)

A zwitterionic polymer filtrate reducer with enhanced anti-polyelectrolyte effect for high-temperature and high-salinity conditions - Shangdong Gao; Dan Lin; Ao Li; Liandong Deng; Anjie Dong; Jianhua Zhang (Chemical Engineering Journal, 2025)

Biocompatible and stretchable chitosan piezoelectric gel with antibacterial capability and motion monitoring function for Achilles tendon rupture treatment - Zhencheng Xiong; Bingqing Lin; Cheng Huang; Ao Duan; Chaoyi Zhang; Guangliang Qiang; Wenzheng Liu; Renliang Zhao; Xiangtian Deng; Dong Wang; Zilu Ge; Guanglin Wang; et al. (Carbohydrate Polymers, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Construction of 3D MXene-SO3/graphene oxide/cyclodextrin heterogeneous hybrid aerogels for green and efficient catalysis production of ethyl acetate - Qi Ao; Xiaoxiao Lv; Lin Jiang; Jun Tang (Chemical Engineering Journal, 2025)

Integrating sentinel-2a imagery, DEM data, and spectral feature analysis for landslide detection via fully convolutional networks - Yu Qu; Hanfa Xing; Lin Sun; Xian Shi; Jianfeng Huang; Zurui Ao; Zexiu Chang; Jiaju Li (Landslides, 2025)

Salinity impacts on n-alkanes in lake sediments of the Badain Jaran Desert, Northwestern China: Implications for paleoclimate reconstruction - Meng Li; Zhuolun Li; Shipei Dong; Lin Chen; Xianbao Su; Chen'ao Lu; Aifeng Zhou; Nai'ang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of pre-chlorination on ultrafiltration process in directly treating seasonal high-turbidity surface water: Membrane fouling control and shock load resisting - Haochun Wang; Yaru Zhang; Chenghai Lin; Ao Wang; Yanrui Wang; Yating Hu; Shu Jiang; Jinlong Wang; Heng Liang; Xiaobin Tang (Journal of Water Process Engineering, 2024)

Base on photothermal interfacial molecular transfer for efficient biodiesel catalysis via enzyme@cyclodextrin metal-organic frameworks loaded MXene - Qi Ao; Lin Jiang; Ying Song; Xinglai Tong; Tuohao Jiang; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2024)

OsNAC15 regulates drought and salt tolerance in rice - Chuan-Wei Ao; Gan-ju Xiang; Yan-Fei Wu; Yue Wen; Zhong-Lin Zhu; Feng Sheng; Xuezhu Du (Physiology and Molecular Biology of Plants, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Microalgae treatment of food processing wastewater for simultaneous biomass resource recycling and water reuse - Hang Xu; Chen Liu; Ao Wang; Baofeng Yue; Tao Lin; Mingmei Ding (Journal of Environmental Management, 2024)

Improved activity and significant O2 resistance of Cs doped Co3O4 catalyst for N2O decomposition - Hongyu Zhao; Pan Wang; Zonglin Li; Chengcheng Ao; Xuteng Zhao; He Lin (Journal of Environmental Chemical Engineering, 2024)

Large-Scale carbon Fiber-Based Solar-Driven evaporator with 1T MoS2-MXene Heterostructure: Towards reliable mechanical performance and efficient seawater desalination - Lin Jin; Lin Zhang; Hao Liang; Yuhui Ao; Song Wang; De Sun (Chemical Engineering Journal, 2024)

Hollow tubular MnOx prepared by flame annealing with cotton fiber as sacrificial template and its applications for Hg0 adsorption in flue gas - Shengyan Liu; Wensheng Lin; Ao Wang; Wei Chen; Liangying Yu; Chong Tian (Chemical Engineering Journal, 2024)

Experimental study on wood chips gasification over Ni/dolomite - Zhiyuan Luo; Ye Tian; Lin Mi; Guanyan Chen; Xiong Zhou; Ao Bian (Clean Technologies and Environmental Policy, 2024)

Influence of arbuscular mycorrhizal fungi on root foraging and competitive ability depends on soil phosphorus distribution: evidence from two pairs of invasive and native plants - Na-Na Yao; Ao Liu; Xiao-Jing Wang; Hao-Hui Deng; Sheng-Qi Fan; Hai-Jie Zhang; Hui-Xuan Liao; Shao-Lin Peng; Bao-Ming Chen (Applied Soil Ecology, 2024)

Neonicotinoids as emerging contaminants in China’s environment: a review of current data - Lingzhi Liao; Ting Sun; Zhenhui Gao; Jianing Lin; Meng Gao; Ao Li; Teng Gao; Ziqin Gao (Environmental Science and Pollution Research, 2024)

Effect of loading frequency and cyclic stress ratio on undrained cyclic behaviors of clay-structure interface with various overconsolidation ratios - Shi-ao Liu; Chencong Liao; Wenxing Lin; Jinjian Chen; Xiaohe Xia (Soil Dynamics and Earthquake Engineering, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Insight into the synergistic effects of surface microstructures and wall peristalsis on glucose production in a bionic microreactor - Kai Lin; Ao Xia; Yun Huang; Xianqing Zhu; Xun Zhu; Kaiyong Cai; Zidong Wei; Qiang Liao (Chemical Engineering Journal, 2024)

Microbial strategies for effective hexavalent chromium removal: A comprehensive review - Shilin Zha; Ao Yu; Zhongbing Wang; Qi Shi; Xunniu Cheng; Chunli Liu; Chunjian Deng; Guisheng Zeng; Shenglian Luo; Zongwen Zhao; Lin Zhou (Chemical Engineering Journal, 2024)

Highly biologically functional magnesium silicate-coated 3D printed round pore-shaped titanium scaffold alters exosomal miRNA expression to promote osteogenic differentiation for bone defect repair - Xuwei Luo; Zhencheng Xiong; Dong Wang; Renliang Zhao; Xiangtian Deng; Ao Duan; Chaoyi Zhang; Wenzheng Liu; Zilu Ge; Zhen Zhang; Qian Fang; Dongqin Xiao; et al. (Chemical Engineering Journal, 2024)

PARP-2 mediates cardiomyocyte aging and damage induced by doxorubicin through SIRT1 Inhibition - Chaoming Huang; Xuan Zhang; Shulin Wang; Ao Shen; Tianfen Xu; Yanhong Hou; Shuhan Gao; Yongwan Xie; Yi Zeng; Jiayu Chen; Runxiang Lin; Yu Zhang; et al. (Apoptosis, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

New solution for predicting the removal efficiency of organic contaminants by UV/ H2O2: From a case study of 1H-benzotriazole - Juan Dang; Ling Lin; Li-ao Gao; Lin Qi; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Science of The Total Environment, 2024)

Corrigendum to “Effects of interface conditions on tribological and hysteretic behaviors of symmetric friction connections” Eng Struct 302 (2024) 117405 - Hongliang Liu; Liang-Jiu Jia; Yu-Ao Lin; Ping Xiang (Engineering Structures, 2024)

Effects of interface conditions on tribological and hysteretic behaviors of symmetric friction connections - Hongliang Liu; Liang-Jiu Jia; Yu-Ao Lin; Ping Xiang (Engineering Structures, 2024)

In situ Fe isotope analysis of Cr-rich iron oxides using pure chromium metal for isobaric interference corrections by femtosecond LA–MC–ICP–MS - Xinting Lü; Detao He; Yongsheng Liu; Ming Li; Jie Lin; Wei Chen; Lüyun Zhu; Ao Yang; Yantong Feng; Zhenyi Liu; Xianli Zeng; Zhaochu Hu (Chemical Geology, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Perturbation of IP3R-dependent endoplasmic reticulum calcium homeostasis by PPARδ-activated metabolic stress leads to mouse spermatocyte apoptosis: A direct mechanism for perfluorooctane sulfonic acid-induced spermatogenic disorders - Wang Yang; Xi Ling; Shijun He; Haonan Cui; Lihong Wang; Zeyu Yang; Huihui An; Peng Zou; Qing Chen; Lei Sun; Huan Yang; Jinyi Liu; et al. (Environmental Pollution, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Critical review on advances and perspectives of ultrasound assisted membrane technologies for water purification - Ao Wang; Hang Xu; Cungen Chen; Liu Chen; Tao Lin; Jun Ma; Mingmei Ding (Chemical Engineering Journal, 2024)

Design and analysis of an electro-adhesive hexapod robot with convertible limbs in microgravity - Ao Xiang; Lin Zhang; Li Fan (Advances in Space Research, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Triplex visual detection of tobacco potyviruses using reverse transcription recombinase polymerase amplification assay combined with lateral flow dipstick - Tengzhi Xu; Xingwei Lin; Xiaolian Zhang; Yong Fu; Hao Luo; Chun Luo; Zhengduo Luo; Lei Lei; Meng-ao Jia (Crop Protection, 2023)

Construction of molecular enrichment accelerators via assembly of enzyme surface grafted polymer and cyclodextrin achieving rapid and stable ester catalysis for biodiesel synthesis - Qi Ao; Lin Jiang; Xinglai Tong; Ying Song; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2023)

Recalcitrant organic carbon plays a key role in soil carbon sequestration along a long-term vegetation succession on the Loess Plateau - Jingwei Shi; Mingyang Song; Lin Yang; Fei Zhao; Jianzhao Wu; Jiwei Li; Zhijing Yu; Ao Li; Zhouping Shangguan; Lei Deng (CATENA, 2023)

Review on in situ Isotopic Analysis by LA-MC-ICP-MS - Jie Lin; Ao Yang; Ran Lin; Ji Mao; Zhaochu Hu; Yongsheng Liu (Journal of Earth Science, 2023)

Study on potential antigenicity and functional properties of whey protein treated by high hydrostatic pressure based on structural analysis - Xin-Xin Yu; Xiao-Hui Wang; Sheng-Ao Zhang; Ying-Hua Zhang; Han-Lin Zhang; Yu-Qi Yin (Food Research International, 2023)

Thermodynamic and kinetic analyses of Janus membrane scaling in membrane distillation for zero liquid discharge engineering - Ao Wang; Hang Xu; Jun Ma; Jiawei Fu; Tao Lin; Mingmei Ding (Desalination, 2023)

3D hierarchical fireproof gel polymer electrolyte towards high-performance and comprehensive safety lithium-ion batteries - Yirou Du; Xianshuai Liu; Lin Chen; Sihao Yin; Yuhui Xie; Ao Li; Xiaodong Liang; Yong Luo; Feng Wu; Yi Mei; Delong Xie (Chemical Engineering Journal, 2023)

Advances in high performance anion exchange membranes: Molecular design, preparation methods, and ion transport dynamics - Ximin Chen; Yingqing Zhan; Junlei Tang; Xulin Yang; Ao Sun; Bing Lin; Fei Zhu; Hongshan Jia; Xianzhang Lei (Journal of Environmental Chemical Engineering, 2023)

TERT transcription and translocation into mitochondria regulate benzo[a]pyrene/BPDE-induced senescence and mitochondrial damage in mouse spermatocytes - Haonan Cui; Wang Yang; Shijun He; Zili Chai; Lihong Wang; Guowei Zhang; Peng Zou; Lei Sun; Huan Yang; Qing Chen; Jinyi Liu; Jia Cao; et al. (Toxicology and Applied Pharmacology, 2023)

Nano zero-valent iron enhances the absorption and transport of chromium in rice (Oryza sativa L.): Implication for Cr risks management in paddy fields - Ting Liu; Zeting Guan; Jingjing Li; Ming Ao; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

CNN-based automated trace editing method using Hough transform - Yang Shen; Xiao-lin Hu; Tong-dong Wang; Jia-jia Cui; Si-hao Tao; Ao Li; Qiang Lu; De-zhi Zhang; Wei-guo Xiao (Applied Geophysics, 2023)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

Impact of climatic and vegetation dynamic change on runoff over the Three Rivers Source Region based on the Community Land Model - Mingshan Deng; Xianhong Meng; Yaqiong Lu; Lele Shu; Zhaoguo Li; Lin Zhao; Hao Chen; Lunyu Shang; Danrui Sheng; Xinmao Ao (Climate Dynamics, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

Collaborative optimization method and energy-saving, carbon-abatement potential evaluation for nearly-zero energy community supply system with different scenarios - Di Wu; Guangyao Fan; Yuxuan Duan; Ao Liu; Peiwen Zhang; Jiacheng Guo; Chengkai Lin (Sustainable Cities and Society, 2023)

How can vanillin improve the performance of lignocellulosic biomass conversion in an immobilized laccase microreactor system? - Kai Lin; Ao Xia; Yun Huang; Xianqing Zhu; Xun Zhu; Kaiyong Cai; Zidong Wei; Qiang Liao (Bioresource Technology, 2023)

Layered porous carbon material derived from food residues and its application for elemental mercury adsorption in flue gas - Ao Wang; Wei Chen; Shengyan Liu; Wensheng Lin; Chong Tian (Fuel, 2023)

Tailoring the crumpled structures of a polyamide membrane with a heterostructural MXene-TiO2 interlayer for high water permeability - Jiawei Fu; Hang Xu; Tao Lin; Ao Wang; Anqi Wang; Chen Yao; Weihang Chen; Mingmei Ding; Chunxia Geng; Li Gao (Desalination, 2023)

Enhanced degradation of emerging contaminants by percarbonate/Fe(II)-ZVI process: case study with nizatidine - Mingxin Huo; Deqiang Zou; Yingzi Lin; Yi Lou; Gen Liu; Siwen Li; Lei Chen; BaoLing Yuan; Qingyu Zhang; Ao Hou (Environmental Science and Pollution Research, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

CH4 adsorption and diffusion characteristics in stress-loaded coal based on molecular simulation - Hai-fei Lin; Hang Long; Shu-gang Li; Yang Bai; Tong Xiao; Ao-li Qin (Fuel, 2023)

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

Enhanced high-salinity brines treatment using polyamide nanofiltration membrane with tunable interlayered MXene channel - Ao Wang; Hang Xu; Jiawei Fu; Tao Lin; Jun Ma; Mingmei Ding; Li Gao (Science of The Total Environment, 2023)

Multi-primary human-centric lighting based on the optical power ratio and the CCT super-smooth switching algorithms - Fangyuan Zhu; Youqin Lin; Weizhi Huang; Tingwei Lu; Zongyuan Liu; Xiaokun Ji; Ao Kang; Huanhua Wang; Zhong Chen; Tingzhu Wu (Building and Environment, 2023)

Highly promoted phytoremediation with endophyte inoculation in multi-contaminated soil: plant biochemical and rhizosphere soil ecological functioning behavior - Chenjing Liu; Qian Song; Linhuazhi Ao; Nan Zhang; Haowen An; Hai Lin; Yingbo Dong (Environmental Science and Pollution Research, 2022)

What Caused the Inconsistency between Rb−Sr and 40Ar−39Ar Ages of Authigenic Illites? - Entao Liu; I. Tonguç Uysal; Jian-Xin Zhao; Zi’ao Zhang; Xudong Lin (Journal of Earth Science, 2022)

Identification of Key Pathways and Genes in SARS-CoV-2 Infecting Human Intestines by Bioinformatics Analysis - Ji-Chun Chen; Tian-Ao Xie; Zhen-Zong Lin; Yi-Qing Li; Yu-Fei Xie; Zhong-Wei Li; Xu-Guang Guo (Biochemical Genetics, 2022)
COVID-19 is a serious infectious disease that has recently swept the world, and research on its causative virus, SARS-CoV-2, remains insufficient. Therefore, this study uses bioinformatics analysis techniques to explore the human digestive tract diseases that may be caused by SARS-CoV-2 infection. The gene expression profile data set, numbered GSE149312, is from the Gene Expression Omnibus (GEO) database and is divided into a 24-h group and a 60-h group. R software is used to analyze and screen out differentially expressed genes (DEGs) and then gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses are performed. In KEGG, the pathway of non-alcoholic fatty liver disease exists in both the 24-h group and 60-h group. STRING is used to establish a protein–protein interaction (PPI) network, and Cytoscape is then used to visualize the PPI and define the top 12 genes of the node as the hub genes. Through verification, nine statistically significant hub genes are identified: AKT1, TIMP1, NOTCH, CCNA2, RRM2, TTK, BUB1B, KIF20A, and PLK1. In conclusion, the results of this study can provide a certain direction and basis for follow-up studies of SARS-CoV-2 infection of the human digestive tract and provide new insights for the prevention and treatment of diseases caused by SARS-CoV-2.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Identifying the priority areas for enhancing the ecosystem services in hilly and mountainous areas of southern China - Jia-ling Tian; Yu Peng; Yi-hang Huang; Ting Bai; Lian-lin Liu; Xiao-ao He; Shi-qian Luo (Journal of Mountain Science, 2022)

Taxonomic description of Pseudomonas rhizovicinus sp. nov., isolated from the rhizosphere of a desert shrub Haloxylon ammodendron - Ao-Lei He; Hui-Ru Li; Hui-Ping Li; Jing-Yi Gou; Jia Chen; Qi Zhao; Jin-Lin Zhang (Antonie van Leeuwenhoek, 2021)

Houcaris gen. nov. from the early Cambrian (Stage 3) Chengjiang Lagerstätte expanded the palaeogeographical distribution of tamisiocaridids (Panarthropoda: Radiodonta) - Yu Wu; Dongjing Fu; Jiaxin Ma; Weiliang Lin; Ao Sun; Xingliang Zhang (PalZ, 2021)

A DEM fusion method for ascending and descending orbit StereoSAR DEMs in complicated mountain areas considering SAR echo intensity - Guo-lin Cai; Dong Shen; Ao-li Zhang; Hai-hua Yu; Xuan-yu Zhang (Journal of Mountain Science, 2021)

A new three-dimensional computerized ionospheric tomography model based on a neural network - Dunyong Zheng; Yibin Yao; Wenfeng Nie; Nan Chu; Dongfang Lin; Minsi Ao (GPS Solutions, 2021)

Development of 85 SNP markers for the endangered plant species Prunus mira (Rosaceae) based on restriction site-associated DNA sequencing (RAD-seq) - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Yu-e Bai (Conservation Genetics Resources, 2020)

Development and characterization of 72 SNP markers in Armeniaca sibirica based on transcriptomics - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Shulan Bai; Yu-e Bai (Conservation Genetics Resources, 2020)

Effect of Calcium-Based Catalysts on Pyrolysis Liquid Products from Municipal Sludge - Wei Luo; Yi-Feng Su; Qing Hu; Huai-Lin Yin; Shuo Wang; Li-Jiao Ao; Xiao-Xi Wen; Sheng-Xiong Huang; Nan Zhou; Wei Zhang; Zhi Zhou (BioEnergy Research, 2020)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Comparison of Inorganic and Organically Bound Trace Minerals on Tissue Mineral Deposition and Fecal Excretion in Broiler Breeders - Geng Wang; Lujie Liu; Zhongpei Wang; Xun Pei; Wenjing Tao; Zhiping Xiao; Bojing Liu; Minqi Wang; Gang Lin; Tuoying Ao (Biological Trace Element Research, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Effect of roughness lengths on surface energy and the planetary boundary layer height over high-altitude Ngoring Lake - Zhaoguo Li; Shihua Lyu; Lijuan Wen; Lin Zhao; Xianhong Meng; Yinhuan Ao (Theoretical and Applied Climatology, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity - Kaige Peng; Likui Yang; Jian Wang; Feng Ye; Guorong Dan; Yuanpeng Zhao; Ying Cai; Zhihong Cui; Lin Ao; Jinyi Liu; Zhongmin Zou; Yan Sai; et al. (Molecular Neurobiology, 2017)

Effects of Supplemental Chromium Propionate on Serum Lipids, Carcass Traits, and Meat Quality of Heat-Stressed Broilers - Fang Xiao; Degulina Ao; Bo Zhou; Jerry W Spears; Xi Lin; Yanling Huang (Biological Trace Element Research, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Turbulent transfer coefficient and roughness length in a high-altitude lake, Tibetan Plateau - Zhaoguo Li; Shihua Lyu; Lin Zhao; Lijuan Wen; Yinhuan Ao; Shaoying Wang (Theoretical and Applied Climatology, 2016)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Liver proteomic analysis of the large yellow croaker (Pseudosciaena crocea) following polyriboinosinic:polyribocytidylic acid induction - Yinnan Mu; Xiang Wan; Kebing Lin; Jingqun Ao; Xinhua Chen (Fish Physiology and Biochemistry, 2013)

Diagnosis of nervous necrosis virus in orange-spotted grouper, Epinephelus coioides, by a rapid and convenient RT-PCR method - Yinnan Mu; Kebing Lin; Xinhua Chen; Jingqun Ao (Acta Oceanologica Sinica, 2013)

CXCR4 positive cells from Lewis lung carcinoma cell line have cancer metastatic stem cell characteristics - Wei-Qi Nian; Fang-Lin Chen; Xu-Jun Ao; Zheng-Tang Chen (Molecular and Cellular Biochemistry, 2011)